-182=-6(7-6n)-n

Simple and best practice solution for -182=-6(7-6n)-n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -182=-6(7-6n)-n equation:


Simplifying
-182 = -6(7 + -6n) + -1n
-182 = (7 * -6 + -6n * -6) + -1n
-182 = (-42 + 36n) + -1n

Combine like terms: 36n + -1n = 35n
-182 = -42 + 35n

Solving
-182 = -42 + 35n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-35n' to each side of the equation.
-182 + -35n = -42 + 35n + -35n

Combine like terms: 35n + -35n = 0
-182 + -35n = -42 + 0
-182 + -35n = -42

Add '182' to each side of the equation.
-182 + 182 + -35n = -42 + 182

Combine like terms: -182 + 182 = 0
0 + -35n = -42 + 182
-35n = -42 + 182

Combine like terms: -42 + 182 = 140
-35n = 140

Divide each side by '-35'.
n = -4

Simplifying
n = -4

See similar equations:

| 4z^2-16+12=0 | | 7x+3/2-9x-8/4=6 | | -22-x=3w-w+4w | | 4/5x+4/3+2x | | 1/5x-y=76 | | -7p-(-7+5p)=-4(3p-7) | | 5(1+7)-5=175 | | x+4/15=-1 | | (7x^2-7x+8)+(9x^3-5x)= | | 3(x+3)+12=6x+3 | | 5(2a-4b)= | | -4(n+6)=12 | | 19=4+3v | | -x-4+3x=x-3+1 | | 7(x+5)=13 | | 4-6a+4a=-115(7-2a) | | 5x+47= | | 11/6x6/35 | | 4(2a-6)+8b= | | (3x+39/8)=0 | | 7k-2(3k+1)= | | 5x-1+x=15 | | 11=((7w-9)/2)+((8w+1)/5) | | y/8+4=6 | | 9(2/3+x)=24 | | 4x+9=8-6x | | 18-.10x=34 | | 3[7r-7]=-6+6r | | 7n-5n=9(n+7)-7(n+10) | | -5x1/4x4 | | -2/8n=3 | | 5n-3=3n-55 |

Equations solver categories